Advancements in Energy-Efficient Electrical Motor Design: A Comprehensive Review - Amit Pathak; Anoop H. Budhrani; Alpesh S. Adeshara; Hardik M. Pandya; Deepak M. Varu (International Journal of Electrical Machine Analysis and Design, 2024)
The rapid growth in energy demand poses a fundamental challenge for the whole power industry in fulfilling the increased demand. An exhaustive energy audit recommends substituting energy-efficient gadgets with conventional ones, which function with low efficiency and waste a significant amount of electricity. Electric motors are quite common in contemporary life, providing energy to a wide range of devices, including both domestic and industrial machinery. Nevertheless, they bear the responsibility for substantial energy usage, amounting to as much as 40% of worldwide power consumption. Hence, it is imperative to enhance the efficacy of electric motors to decrease energy consumption and the corresponding emissions of greenhouse gases. This study will analyse the key elements associated with the design of energy-efficient electrical motors. Furthermore, this document will examine several prevalent variants of electric motors, encompassing their structure, properties, and practical uses.
Keywords: Electrical motor; economical; efficiency; energy-efficient; motor design